Effects of bleaching treatment on the properties of bio-polyurethane films from liquefied bamboo - James, Redzuan Mohammad Suffian; Md Tahir, Paridah; Mohd Yusof, Norwahyuni; Osman Al-Edrus, Syeed Saifulazry; Zainal Abidin, Zurina; Palle, Ismawati; Uyup, Mohd Khairun Anwar; Lee, Seng Hua (College of Natural Resources, 2024)
Malaysian bamboo residues were subjected to a liquefaction process. Bleaching of the liquefied product was carried out to reduce its coloration. Polyurethane (PU) films were then manufactured as a coating material by reacting the-OH groups in the bamboo material with isocyanate (-NCO). The study’s objective was to investigate the effects of bleaching on the properties of resulting polyurethane films and to elucidate its behavior as affected by the NCO/OH ratios. Bamboo residues, in powder form, were liquefied with polyethylene glycol (PEG 400) and glycerol (Gly) as reactive co-solvent, and sulphuric acid as catalyst. The obtained liquefied bamboo was then bleached with hydrogen peroxide. Bleached and unbleached liquefied bamboo were used to produce PU film by reacting isocyanate at NCO/OH ratios of 1.6, 1.8, 2.0, and 2.2. The results revealed that the NCO/OH ratios improved the mechanical performance of the PU films. Bleaching treatment slightly reduced the thermal stability and mechanical strength of the PU films. However, bleached PU films displayed lower water absorption and lower biodegradation than unbleached PU films. Nevertheless, the performance of the bleached PU films was still acceptable, indicating that the bleaching treatment using hydrogen peroxide is feasible to obtain semi-transparent film.